PEMBERIAN REHABILITASI TERHADAP ANAK PELAKU TINDAK PIDANA NARKOTIKA (STUDI KASUS TIGA PUTUSAN PENGADILAN) - Jefrianto Sembiring; Mahmud Mulyadi; Marlina Marlina; Edy Ihkhsan (USU LAW JOURNAL, 2017)
ABSTRACT   Legal basis over the granting of rehabilitation against the perpetrators of the crime of narcotics is according to the provisions of Act No. 35 of 2009, and Act No. 11 in 2012. Rehabilitation is a facility to its semi closed, meaning only certain people with special interests who can enter this area. Rehabilitation of narcotics is a place that provides skills training and knowledge to prevent yourself from narcotics. According to Act No. 35 of 2009, there are two types of rehabilitation medical rehabilitation and rehabilitation that is social. The consideration of judges in evaluating the trial in the case of narcotics that kids do is dropping the criminal narcotics by doing rehabilitation against the defendant. The judge stated that in the legislation of criminal justice system of children of a troubled with the law is referred to as a bad boy. The judge stated that truly matter in the indictment the public prosecutor, the judge nevertheless looked in the criminal penalties against giving users of narcotics offenders children, then by observing the main principle for the children's best interests for the child, namely in the dropping of sanctions, then the provisions of the rehabilitation of medical and social rehabilitation for the defendant can be applied.   Key Words: Rehabilitation, Children, Crime Of Narcotics